The in vitro Activity of Vaginal Lactobacillus With Probiotic Properties Against Candida. Issue 2 (2005) - Strus, Magdalena; Kucharska, Agnieszka; Kukla, Grażyna; Brzychczy-Włoch, Monika; Maresz, Katarzyna; Heczko, Piotr B.
Abstract : Lactobacilli, the predominant vaginal microorganisms in healthy premenopausal women, control other members of the vaginal microflora and thus protect against bacterial vaginosis and urinary tract infections. It has been claimed that some lactobacilli are also protective against Candida vaginitis. Little is known, however, about the mechanisms by which these lactobacilli can control vaginal populations of Candida and prevent vaginitis. To address this question, vaginal Lactobacillus strains with known antagonistic properties against bacteria were tested for their cell surface properties, adhesion to vaginal cell lines in vitro and antagonistic activities against Candida . A small proportion of the lactobacilli tested adhered strongly to cultured vaginal epithelial cells and inhibited growth of Candida albicans but not of C. pseudotropicalis . This anticandidal activity was in some Lactobacillus strains related to hydrogen peroxide (H 2 O 2 ) production, but catalase treatment did not suppress this activity in other Lactobacillus strains, suggesting alternative mechanism(s). Moreover, tested vaginal Candida strains were resistant to relatively high concentrations ofH 2 O 2 that markedly exceeded those produced by even the most active Lactobacillus strains.